SPATIO‐TEMPORAL VARIATIONS OF SEVEN WEATHER VARIABLES IN IRAN: APPLICATION OF CRU TS AND GPCC DATA SETS†. (21st January 2020) - Ababaei, Behnam
Abstract: Iran's climate‐sensitive agriculture and water resources are vulnerable to climate change and investigation of climatic trends helps in preparing adaptation strategies. Weather stations are sparsely distributed and access to complete weather data is limited. In such situations, gridded global/regional data sets are promising alternatives. Here, monthly time series of seven weather variables (i.e. monthly averages or monthly totals of daily values) were obtained from the Climatic Research Unit TS V4.01 and Global Precipitation Climatology Centre V7 gridded data sets in 675 grid cells covering the country and analysed over the periods 1957–1986 and 1987–2016 at annual, seasonal and monthly scales. Over the two periods and at a national scale, mean temperature has increased by 0.004 ( P  = 0.717) and 0.04 °C yr −1 ( P  = 0.000), while the diurnal temperature range has not significantly changed ( P  > 0.6). Annual total precipitation experienced an insignificant increase (0.81 mm yr −1 ; P  = 0.666) over the first period but declined by 2.12 mm yr −1 ( P  = 0.041) over the second. Potential evapotranspiration (PET) has increased by 0.32 ( P  = 0.398) and 1.43 mm yr −1 ( P  = 0.015), respectively. Since 1987, significant increasing trends in temperature were detected all over the country. While significant increasing trends in annual precipitation were detected in the central regions and south‐west over the first period, decreasing trends prevailed during 1987–2016 in the south, southwest and east with winter being the largest contributor to annual trends. Over the last three decades, annual PET has increased mostly in the north‐west and south‐east while significant increasing trends were detected in 89% of grid cells, except in a few cells in the north‐east. Cloud cover, vapour pressure and frequency of frost days were also analysed. These results are crucial for policy‐makers, researchers and engineers in the country and internationally who usually base their decisions and designs on outdated data sparsely distributed in space. © 2020 John Wiley & Sons, Ltd. Résumé: L'agriculture et les ressources en eau sensibles au climat de l'Iran sont vulnérables au changement climatique et l'investigation des tendances climatiques facilite la préparation de stratégies d'adaptation. Les stations météorologiques sont peu dispersées et l'accès à des données météorologiques complètes est limité. Dans de telles situations, les ensembles de données globaux/régionaux maillés constituent des alternatives prometteuses. Ici, des séries temporelles mensuelles de sept variables météorologiques (moyennes mensuelles ou totaux mensuels de valeurs journalières) ont été obtenues de l'unité de recherche climatique TS V4.01 et des ensembles de données maillées du Global Precipitation Climatology Centre V7 à 675 cellules couvrant le pays et analysées sur les périodes 1957–1986 et 1987–2016 aux échelles annuelle, saisonnière et mensuelle. Au cours des deux périodes et à l'échelle nationale, la température moyenne a augmenté de 0.004 ( P  = 0.717) et de 0.04 °C −1 ( P  = 0.000), tandis que la plage de températures diurnes n'a pas changé de manière significative ( P  > 0.6). Les précipitations totales annuelles ont connu une augmentation insignifiante (0.81 mm an‾¹; P  = 0.666) au cours de la première période, mais ont diminué de 2.12 mm an‾¹ ( P  = 0.041) au cours de la deuxième période. L'évapotranspiration potentielle (PET) a augmenté de 0.32 ( P  = 0.398) et 1.43 mm an −1 ( P  = 0.015), respectivement. Depuis 1987, des tendances à la hausse significatives de la température ont été détectées dans tout le pays. Bien que des tendances à la hausse significatives des précipitations annuelles aient été détectées dans les régions du centre et du sud‐ouest au cours de la première période, des tendances à la baisse ont été observées de 1987 à 2016 dans le sud, le sud‐ouest et l'est, l'hiver contribuant le plus aux tendances annuelles. Au cours des trois dernières décennies, le PET annuel a augmenté principalement dans le nord‐ouest et le sud‐est, tandis que des tendances à la hausse significative ont été détectées dans 89% des cellules de la grille, sauf dans quelques cellules du nord‐est. La couverture nuageuse, la pression de vapeur et la fréquence des jours de gel ont également été analysées. Ces résultats sont cruciaux pour les décideurs, les chercheurs et les ingénieurs du pays et du monde entier qui basent généralement leurs décisions et leurs conceptions sur des données obsolètes dispersées dans l'espace. © 2020 John Wiley & Sons, Ltd.